Efficacy of a Traditional Herbal Formula, Banha-Sasim-Tang in Functional Dyspepsia Classified as Excess Pattern - Kim, Yun Hee; Kim, Jun Young; Kwon, O-Jin; Jung, So Young; Joung, Jin-Yong; Yang, Chang Sop; Lee, Jun-Hwan; Cho, Jung-Hyo; Son, Chang-Gue (Frontiers in Pharmacology, 2021)
This study evaluated the efficacy and safety of Banha-sasim-tang (BST) in patients with functional dyspepsia (FD). BST (Banxia-xiexin-tang in traditional Chinese medicine and Hange-shashin-to in Kampo medicine) is traditionally prescribed for the treatment of dyspepsia with epigastric stiffness and gastric fullness in China, Japan, and Korea. Patients with FD were randomly administered an oral dose (10 g) of BST syrup or placebo, twice a day for 4 weeks. The primary outcome was the symptom checklist part of the Nepean dyspepsia index (NDI). The secondary outcomes were the quality of life (QoL) part of the NDI, functional dyspepsia-related QoL (FD-QoL), and visual analog scale (VAS). A total of 60 patients with FD were screened, and 50 were randomized into BST group (n = 25) and placebo group (n = 25). Two patients in the placebo group withdrew before the start of the treatment. Administration of BST syrup resulted in improvement in the symptom-related NDI score in the BST group compared with that in the control group; however, the difference was not significant. BST syrup significantly improved “fullness after eating” index of NDI at follow-up time point (2.88 ± 2.65 vs 4.78 ± 2.69, p = 0.0081). In the total score of the QoL section of the NDI and FD-QoL scales, there was no significant improvement in the BST group compared to that in the placebo group. With regard to improvement in overall FD symptoms, the VAS scale showed improvement in both groups, but the difference was not significant. Interestingly, follow-up investigation showed a significantly beneficial effect of BST on FD symptoms, when compared to placebo. Significant improvement observed in VAS score (39.60 ± 22.29 vs 52.17 ± 20.55, p = 0.048). This indicated that the effect of BST lasted even after the completion of the medication regimen. Overall, our data suggest that while BST showed no significant improvement in the symptom-related NDI score and the QoL related scores in NDI and FD-QoL after 4 weeks of treatment, it effectively improved the VAS score and fullness after eating-related symptoms in the follow-up visit. Clinical Trial Registration:https://cris.nih.go.kr; Identifier KCT 0002013